Aristolactams and further constituents from Aristolochia chamissonis - TSURUTA,Angélica Yucari (2002)
From the ethanol extract of the stems of Aristolochia chamissonis, spathulenol, sitosterol, beta-sitosteryl-D-glucoside, kolavelool, 13-epi-2-oxo-kolavelool, trans-N-p-coumaroyltyramine, allantoin, aristolochic acid I, and aristolactam AII were isolated. The structures of aristolactam AII and piperolactam A have been revised by means of spectroscopic methods and chemical derivatizations.